ADMINISTRATORS’ LEADERSHIP SKILLS AND EMPLOYEES’ JOB ENGAGEMENT IN TERTIARY EDUCATIONAL INSTITUTIONS IN OGUN STATE NIGERIA - Adekunle, Akeem A. (PEOPLE: International Journal of Social Sciences, 2017)
The study examined administrators’ leadership skills and employees’ job engagement in tertiary educational institutions is Ogun State, Nigeria. The study was guided by three research questions. A descriptive survey research design was adopted. Four Hundred and Fifteen employees (academic and non-teaching staff) selected from six out of the 12 public tertiary institutions in Ogun State, Nigeria were sampled, using multi-stage sampling technique. A researcher–designed 30 item 4 point modified Likert rating scale instrument entitled “Administrators Leadership Skills and Employees’ Job Engagement Questionnaire” (ALSEJEQ) was used for data collection. The instrument was subjected to reliability test using the Crombach Alpha method and a value of 0.89 was obtained. Data analysis was statistically done using Multiple Regression Analysis. Findings revealed that, though low, the overall model of the three administrators’ leadership skills indicators significantly predicted employees’ job engagement in tertiary educational institutions in Ogun State (F(3, 411) = 47.195, p < 0.05) ; that, though low, the overall model of the administrators’ leadership skills indicators significantly predicted employees’ job engagement in tertiary educational institutions in Ogun State (F(3, 411) = 47.195, p < 0.05); and that although, administrators’ analytical skills significantly contributed to the model, the contribution was negative β = -.284, t (411) = -3.028, p < 0.05. The administrators’ conceptual skills did not significantly contribute to the model β = -.048, t (411) = -.496, p = .620. It was therefore recommended among others that appointment of Administrators of tertiary educational institutions should be hinged on evidence of haven undergone training at the National Institute for Educational Planning and Administration (NIEPA, Nigeria), and that serving institutional Administrators should as a matter of policy be required to engage in Mandatory Continuing Professional Education.